2011
DOI: 10.1007/978-1-4419-7046-6_29
|View full text |Cite
|
Sign up to set email alerts
|

Branch-and-Bound Approach for Parsimonious Inference of a Species Tree from a Set of Gene Family Trees

Abstract: Abstract. We describe a Branch-and-Bound algorithm for computing a parsimonious species tree given a set of gene family trees. Our algorithm can compute a parsimonious species tree for three cost measures: number of gene duplications, number of gene losses, and both combined. Moreover, to cope with intrinsic limitations of Branch-and-Bound algorithms for species trees inference regarding the number of taxa that can be considered, our algorithm can naturally take into account predefined relationships between se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…More recently, a branch-and-bound algorithm to identify exact solutions for the GD problem was introduced [14]. This algorithm was applied to a data-set consisting of 1, 111 gene trees with 29-taxa, but it did not run to completion.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a branch-and-bound algorithm to identify exact solutions for the GD problem was introduced [14]. This algorithm was applied to a data-set consisting of 1, 111 gene trees with 29-taxa, but it did not run to completion.…”
Section: Introductionmentioning
confidence: 99%
“…Here we address the problem of finding a species tree that has a minimum total number of duplications and losses, treating incompleteness as due to true biological loss. Prior results on GTP include a branch-and-bound algorithm in [ 23 ] based on techniques from [ 18 ], a randomized hill-climbing heuristic presented in [ 4 ], a probabilistic and computationally expensive method for co-estimating gene and species trees [ 1 ], and dynamic programming based solutions by Hallett and Lagergren [ 15 ], Bayzid et al [ 20 ] and Chang et al [ 24 ]. However, none of these studies takes the reasons of incompleteness into account, and we have already shown that the standard calculation for losses can be incorrect when incompleteness is due to true biological loss.…”
Section: Algorithms To Find Species Treesmentioning
confidence: 99%
“…Here we introduce iGTP, a stand-alone software application with an easy-to-use graphical user interface (Figure 1 ) that makes it possible to conduct large-scale gene tree parsimony analyses on hundreds of taxa and thousands of gene phylogenies for three of the most important variants of the GTP problem: (i) the duplication problem [ 7 , 25 - 32 ], which minimizes the number of gene duplications, (ii) the duplication-loss problem [ 7 , 25 - 34 ], which minimizes the number of gene duplications and losses, and (iii) the deep-coalescence problem [ 17 , 35 , 36 ], which minimizes the number of deep coalescences. All of these variants of GTP are intrinsically hard [ 37 , 38 ], and exact algorithms [ 15 , 17 , 39 , 40 ] are feasible only when there are very few taxa. Therefore, iGTP relies on widely-used local search heuristics that have been proven to be effective in previous studies [ 36 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%